The Potentiality of Tourism Resources in Hulu Sungai Selatan Regency, South Kalimantan - Ellyn Normelani (Program Pascasarjana, 2017)
Hulu Sungai Selatan regency, South Kalimantan, has potentiality to be developed as tourism destinations. It is especially important for local economic development, cultural preservation, and natural resources conservation. The objective of the research is to identify the tourism potentiality in Hulu Sungai Selatan regency. Result of the study shows that Hulu Sungai Selatan Regency has numerous potential tourism objects, ranging from man-made to natural attractions. On the future development, special interest tourism such as nature-based tourism, ecotourism, culinary tourism religious tourism, history and cultural tourism are potentials to be developed. The sustainable principles of tourism practices should be adopted by local government in every aspect of tourism development. It is especially crucial for natural resources and biodiversity protection; while in the same time enhance the quality of attraction and destination.Keywords: ecotourism, Hulu Sungai Selatan, tourism development, tropical conservation.